Relation of chronic obstructive pulmonary disease to atrial and ventricular arrhythmias - Konecny, Tomas; Park, Jae Yoon; Somers, Kiran R; Konecny, Dana; Orban, Marek; Soucek, Filip; Parker, Kenneth O; Scanlon, Paul D; Asirvatham, Samuel J; Brady, Peter A; Rihal, Charanjit S (The American journal of cardiology, 2014)
Chronic obstructive pulmonary disease (COPD) is associated with increased cardiovascular morbidity and mortality, yet the exact pathophysiological links remain unclear. Whether the presence and severity of COPD are associated with atrial or ventricular arrhythmias recorded on continuous electrocardiographic monitoring is unknown. We identified consecutive adult patients who underwent clinically indicated pulmonary function testing as well as 24-hour Holter monitoring at the Mayo Clinic, Rochester, from 2000 to 2009. Demographic data and relevant co-morbidities were gathered from the electronic medical record; severity of COPD was classified according to the GOLD classification, and arrhythmias were classified in concordance with the current clinical guidelines. From 7,441 patients who were included (age 64±16 years, 49% woman, 92% Caucasian), COPD was diagnosed in 3,121 (41.9%). Compared with those without COPD, the presence and severity of COPD were associated with increased likelihood of atrial fibrillation/atrial flutter (AF/AFL; 23.3% vs 11.0%, respectively, p<0.0001), nonsustained ventricular tachycardia (NSVT; 13.0% vs 5.9%, respectively, p<0.0001), and sustained ventricular tachycardia (0.9% vs 1.6%, respectively, p<0.0001). COPD remained a significant predictor of AF/AFL and NSVT (p<0.0001 and p<0.0001, respectively) after adjusting for age, gender, tobacco use, obesity, hypertension, coronary artery disease, heart failure, diabetes, anemia, cancer, chronic kidney disease, and rate/rhythm control medications. In conclusion, the independent association between the presence and severity of COPD and arrhythmias (AF/AFL and NSVT) provides further insight into the markedly increased cardiovascular mortality of patients with COPD. Further studies should explore which anti-arrhythmic strategies would best apply to the patients with COPD.
Keywords: Female; Plethysmography; elektrokardiografie ambulantní; Atrial Fibrillation; Tachycardia, Ventricular; ženské pohlaví; lidé; Pulmonary Disease, Chronic Obstructive; následné studie; míra přežití; Incidence; retrospektivní studie; chronická obstrukční plicní nemoc; Follow-Up Studies; Male; incidence; Aged; pletysmografie; komorová tachykardie; Survival Rate; Electrocardiography, Ambulatory; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Minnesota; Retrospective Studies; Middle Aged; Humans